The nursing home elder microbiome stability and associations with age, frailty, nutrition and physical location. Issue 1 (January 2018) - Haran, John P.; Bucci, Vanni; Dutta, Protiva; Ward, Doyle; McCormick, Beth
Abstract : Purpose. : The microbiome from nursing home (NH) residents is marked by a loss in diversity that is associated with increased frailty. Our objective was to explore the associations of NH environment, frailty, nutritional status and residents' age to microbiome composition and potential metabolic function. Methodology. : We conducted a prospective longitudinal cohort study of 23 residents, 65 years or older, from one NH that had four floors: two separate medical intensive floors and two floors with active elders. Residents were assessed using the mini nutritional assessment tool and clinical frailty scale. Bacterial composition and metabolic potential of residents' stool samples was determined by metagenomic sequencing. We performed traditional unsupervised correspondence analysis and linear mixed effect modelling regression to assess the bacteria and functional pathways significantly affected by these covariates. Results/Key findings. : NH resident microbiomes demonstrated temporal stability (PERMANOVA P =0.001) and differing dysbiotic associations with increasing age, frailty and malnutrition scores. As residents aged, the abundance of microbiota‐encoded genes and pathways related to essential amino acid, nitrogenous base and vitamin B production declined. With increasing frailty, residents had lower abundances of butyrate‐producing organisms, which are associated with increased health and higher abundances of known dysbiotic species. As residents became malnourished, butyrate‐producing organisms declined and dysbiotic bacterial species increased. Finally, the microbiome of residents living in proximity shared similar species and, as demonstrated for Escherichia coli, similar strains. Conclusion. : These findings support the conclusion that a signature 'NH' microbiota may exist that is affected by the residents' age, frailty, nutritional status and physical location.